Association between human blood metabolome and the risk of pre-eclampsia - Ding, Yaling; Yao, Mengxin; Liu, Jiafeng; Fu, Wanyi; Zhu, Xiaoyan; He, Yelin; Ma, Qiuping; Zhang, Chunhua; Yin, Jieyun (Hypertension research, 2024)
Pre-eclampsia is a complex multi-system pregnancy disorder with limited treatment options. Therefore, we aimed to screen for metabolites that have causal associations with preeclampsia and to predict target-mediated side effects based on Mendelian randomization (MR) analysis. A two-sample MR analysis was firstly conducted to systematically assess causal associations of blood metabolites with pre-eclampsia, by using metabolites related large-scale genome-wide association studies (GWASs) involving 147,827 European participants, as well as GWASs summary data about pre-eclampsia from the FinnGen consortium R8 release data that included 182,035 Finnish adult female subjects (5922 cases and 176,113 controls). Subsequently, a phenome-wide MR (Phe-MR) analysis was applied to assess the potential on-target side effects associated with hypothetical interventions that reduced the burden of pre-eclampsia by targeting identified metabolites. Four metabolites were identified as potential causal mediators for pre-eclampsia by using the inverse-variance weighted method, including cholesterol in large HDL (L-HDL-C) [odds ratio (OR): 0.88; 95% confidence interval (95% CI): 0.83-0.93; P = 2.14 × 10 ), cholesteryl esters in large HDL (L-HDL-CE) (OR: 0.88; 95% CI: 0.83-0.94; P = 5.93 × 10 ), free cholesterol in very large HDL (XL-HDL-FC) (OR: 0.88; 95% CI: 0.82-0.94; P = 1.10 × 10 ) and free cholesterol in large HDL (L-HDL-FC) (OR: 0.89; 95% CI: 0.84-0.95; P = 1.45 × 10 ). Phe-MR analysis showed that targeting L-HDL-CE had beneficial effects on the risk of 24 diseases from seven disease chapters. Based on this systematic MR analysis, L-HDL-C, L-HDL-CE, XL-HDL-FC, and L-HDL-FC were inversely associated with the risk of pre-eclampsia. Interestingly, L-HDL-CE may be a promising drug target for preventing pre-eclampsia with no predicted detrimental side effects. The study consists of a two-stage design that conducts MR at both stages. First, we assessed the causality for the associations between 194 blood metabolites and the risk of pre-eclampsia. Second, we investigated a broad spectrum of side effects associated with the targeting identified metabolites in 693 non-preeclampsia diseases. Our results suggested that Cholesteryl esters in large HDL may serve as a promising drug target for the prevention or treatment of pre-eclampsia with no predicted detrimental side effects.